2013
DOI: 10.15580/gjms.2013.4.022213488
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Effects of Two Fractions ofPhyllanthus amarus (Euphorbiaceae) on the Blood Pressure in Rabbit

Abstract: Phyllanthus amarus is a species used to treat many ailments. The hypotensive effect reported by the pharmacopoeia has been demonstrated for the aqueous extract. This effect is reduced in the presence of atropine. The aim of this work is to evaluate two fractions of P. amarus aqueous extract (EAPA), the aqueous fraction (FAPA) and ethanolic fraction (FEPA), on blood pressure. Phytochemical screening shows that EAPA and FEPA differs by the absence of saponins, while EAPA and FAPA differs by the absence of alkalo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 10 publications
0
14
0
Order By: Relevance
“…A previous study [ 12 ] has suggested that Phyllanthus amarus, described as diuretic agent , might be of interest in the treatment of hypertension. The antihypertensive activity of Phyllanthus amarus has been related to stimulation of muscarinic receptors leading to the formation of endothelium-derived nitric oxide (NO) and also to blocking of calcium channels [ 13 , 14 ]. Moreover, Phyllanthus species have been shown to have several beneficial effects on the vascular function.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous study [ 12 ] has suggested that Phyllanthus amarus, described as diuretic agent , might be of interest in the treatment of hypertension. The antihypertensive activity of Phyllanthus amarus has been related to stimulation of muscarinic receptors leading to the formation of endothelium-derived nitric oxide (NO) and also to blocking of calcium channels [ 13 , 14 ]. Moreover, Phyllanthus species have been shown to have several beneficial effects on the vascular function.…”
Section: Introductionmentioning
confidence: 99%
“…The evaluation of the pharmacological effects of a Phyllanthus amarus aqueous extract administered intravenously in normotensive rabbits has shown that at doses ranging from 4.5 to 71.7 mg/kg, the extract induced a transient decrease in mean arterial blood pressure of about 4.8 ± 0.8 to 14.0 ± 0.6 mmHg [ 14 ]. The ethanolic fraction was the most potent fraction inducing about a 11.5 ± 0.5 mmHg reduction of mean arterial blood pressure at 15 mg/kg [ 14 ]. In addition, it seemed to be the most potent extract for diuresis, however the mechanism action of these diuretic effect remain unclear [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…The phenolic constituent alleviated the effect of anti-mycin A-induced apoptotic cascade (Guha et al, 2010). The gastroprotective activity effect of other phallantus species was studied by Shokunbi and Odetola (2008), the acute toxicity study (Pingale and Shewale., 2011) and its ability to lower blood pressure had been reported (Siridya and Periwal., 1995;Amonkan et al, 2013;Amaechina and Omoybai., 2007). DOI: http://dx.doi.org/10.…”
Section: Introductionmentioning
confidence: 99%
“…The herb has been in use since ages in traditional system as appetizer, stomachic and gastro-protective 26 . The drug is well known to be used as gastro-protective agent.…”
Section: Gastro-protective and Anti-ulcer Activitymentioning
confidence: 99%
“…The drug is well known to be used as gastro-protective agent. The possible mechanism suggests the increase contraction of gastric mucosa and inhibition of inflammatory cells thus reducing ulceration of stomach, inhibition of edema, and removal of leukocytes from sub-mucosal layers and also improving appetite 26 . The increase in gastric contraction suggests increase in surface area and decrease in volume per unit area of inflammatory agent, thus leading to protection of gastric mucosa proving the evident role of herb in traditional medicinal system as stomachic.…”
Section: Gastro-protective and Anti-ulcer Activitymentioning
confidence: 99%